Opened athletic-educational space - the condition of professional development of future teacher of physical culture is needed - Dragnev Y.V (Kharkov National Pedagogical University, 2012)
It is shown that the opening of the sports and educational space is determined by the whole space, where the interaction of the activity of the pedagogical university with different educational institutions on the basis of integration, continuity of the educational process, aimed at physical education, the development of children and young people take place. It is revealed the importance of awareness of such concepts as the world educational space, the international educational space, the European higher education area, European space of higher education and educational space of the CIS countries.